2013
DOI: 10.1007/978-94-007-2592-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Modern Porous Coatings in Orthopaedic Applications

Abstract: The development of porous metals and coatings for orthopaedic applications has revolutionized the medical field. The ability to bond metallic implants to bone has spawned the advancements in total joint arthroplasty we have experienced over the last 4 decades. Early success was obtained as factors (pore size, coefficient of friction, modulus of elasticity) necessary for osseointegration were just being discovered. Despite good results, initial implant designs were fabricated utilizing traditional coatings (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 138 publications
0
16
0
Order By: Relevance
“…The Tritanium structure on the Trident I cup was obtained depositing commercially pure titanium (CPTi) powder on a sacrificial porous polyurethane scaffold via physical vapor deposition; the structure was subsequently sintered at high temperature on the cup, removing the polyurethane. Several steps of powder recoating and sintering provided the final product (Frank et al, ; Muth, Poggie, Kulesha, & Michael Meneghini, ). All the implants, both 3D printed and conventional, are subjected to a final machining stage to obtain the appropriate cup‐liner interface to accommodate the liner component.…”
Section: Discussionmentioning
confidence: 99%
“…The Tritanium structure on the Trident I cup was obtained depositing commercially pure titanium (CPTi) powder on a sacrificial porous polyurethane scaffold via physical vapor deposition; the structure was subsequently sintered at high temperature on the cup, removing the polyurethane. Several steps of powder recoating and sintering provided the final product (Frank et al, ; Muth, Poggie, Kulesha, & Michael Meneghini, ). All the implants, both 3D printed and conventional, are subjected to a final machining stage to obtain the appropriate cup‐liner interface to accommodate the liner component.…”
Section: Discussionmentioning
confidence: 99%
“…However, many successful applications have previously been shown with case studies dealing with orthopedic and dental coatings. 39,40 This study showed that using cheap and easy to prepare heterogeneous polymers, we can create cell selective surface coatings that are able to induce appropriate cell-surface interactions. These surfaces can be used as implant coating materials that can increase success of implant osseointegration.…”
Section: Discussionmentioning
confidence: 97%
“…The main challenge in surface modification for implants comes when the surface is exposed to human body environment. However, many successful applications have previously been shown with case studies dealing with orthopedic and dental coatings …”
Section: Discussionmentioning
confidence: 99%
“…3D printing creates implants with highly porous structures for enhanced fixation, matching bone characteristics such as pore size, coefficient of friction and modulus of elasticity to avoid stress shielding. Porosity and properties similar to cancellous bone may enable bone-implant interactions that lead to primary stability, bone ingrowth and osseointegration [22].…”
Section: Off-the-shelfmentioning
confidence: 99%
“…The component is then finished using wet or coarse blasting on the external surface to obtain roughened areas, and post-processing the internal surface to obtain the required dimensional tolerances and minimal friction for an optimal seating of the liner [27]. The backside coating is applied at a later step using different methods such as solid state processing (powder metallurgy, sintering of powders and fibres), vapour deposition or plasma spray [22,[33][34][35].…”
Section: Manufacturing Processmentioning
confidence: 99%